THE EFFECT OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENTS ON EMPLOYEE PERFORMANCE AT THE MAIN BRANCH BENGKULU - Veronika Dwi Walanda; Suwarni; Kaulan (Penerbit Jurnal Indonesia, 2020)
One of the factors that can affect employee performance is organizational culture. Culture provides an identity for organizational members and generates a commitment to beliefs and values greater than itself, besides that organizational commitment also affects performance. The purpose of this study is to determine the effect of organizational culture and commitment on employee performance at Bank Bengkulu Main Branch. The sample in this study was 56 permanent employees at Bank Bengkulu Main Branch. Data collection used a questionnaire and the method of analysis used is multiple linear regression, test of determination and hypothesis testing. The results of the regression analysis show that the results of the regression analysis show Y = 13.026 + 0.193X1 + 0.508 X2, this illustrates a positive direction of regression, meaning that there is a positive influence between X1 (organizational culture) and X2 (organizational commitment) on the performance (Y) of Bengkulu Bank employees. Main Branch. The value of the coefficient of determination is0.402. This means that organizational culture and organizational commitment have an effect on employees performance at Bank Bengkulu Main Branch by 40.2%, while the remaining 59.8% is influenced by other variables which are not examined in this study. The results of the t test at 0.05 significance level explained that partially organizational culture and organizational commitment had a significant effect on employee performance at Bank Bengkulu Main Branch. The results of F test at 0.05 significance level explain that organizational culture and commitment have a significant simultaneous influence on employee performance at Bank Bengkulu Main Branch.